2019
DOI: 10.1001/jamaneurol.2018.4249
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Racial Disparities in Biomarkers for Alzheimer Disease

Abstract: IMPORTANCE Racial differences in molecular biomarkers for Alzheimer disease may suggest race-dependent biological mechanisms.OBJECTIVE To ascertain whether there are racial disparities in molecular biomarkers for Alzheimer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
307
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 260 publications
(353 citation statements)
references
References 54 publications
26
307
5
Order By: Relevance
“…One study further reported a significant race by APOE ε 4 interaction for both CSF t‐tau and p‐tau, 12 suggesting that the racial disparities in these biomarkers, and hence in the more downstream clinical changes, may depend on APOE ε4 status, consistent with our current findings. Specifically, both biomarker studies 11,12 are cross‐sectional with mean ages from 67.5 to 71.5 years, close to the younger end of the baseline age in the current study where we found that AAs had a lower risk of AD dementia mostly in APOE ε 4 positive participants with a low BMI. Putting all these together, our independent findings on the APOE ε 4 ‐dependent racial disparity in the risk of AD are consistent with the latest biomarker findings.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…One study further reported a significant race by APOE ε 4 interaction for both CSF t‐tau and p‐tau, 12 suggesting that the racial disparities in these biomarkers, and hence in the more downstream clinical changes, may depend on APOE ε4 status, consistent with our current findings. Specifically, both biomarker studies 11,12 are cross‐sectional with mean ages from 67.5 to 71.5 years, close to the younger end of the baseline age in the current study where we found that AAs had a lower risk of AD dementia mostly in APOE ε 4 positive participants with a low BMI. Putting all these together, our independent findings on the APOE ε 4 ‐dependent racial disparity in the risk of AD are consistent with the latest biomarker findings.…”
Section: Discussionsupporting
confidence: 89%
“…One study further reported a significant race by APOE 4 interaction for both CSF t-tau and p-tau, 12 suggesting that the racial disparities in these biomarkers, and hence in the more downstream clinical changes, may depend on APOE 4 status, consistent with our current findings. Specifically, both biomarker studies 11,12 Inherited Alzheimer Network (DIAN) trials, 33 and the Alzheimer's Prevention Initiative (API) trial 34 are ongoing. Primary prevention trials are currently planned.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A few studies have also focused on race and ethnicity differences in biomarkers of Alzheimer's disease. For example, older African Americans have a twofold increase in amyloid beta deposition, but lower concentrations of tau in cerebrospinal fluid compared with Whites, though the latter was found to only be true in participants who were APOE ε4 allele positive . Controlling for cerebrospinal fluid markers of amyloid beta, researchers found that cognitive dysfunction in African Americans was more associated with white matter hyperintensity burden and less associated with tau markers compared with Whites.…”
Section: Race and Ethnicitymentioning
confidence: 99%